2018
DOI: 10.1186/s12974-018-1369-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation is correlated with severity and outcome of cerebral venous thrombosis

Abstract: BackgroundFew studies have suggested a relationship between inflammation and cerebral venous thrombosis (CVT). This retrospective study aimed to explore the changes in inflammation in different CVT stages and the correlation between inflammation and severity and outcome of CVT.MethodsIn total, 95 suitable patients with CVT and 41 controls were compared. Patients with CVT were divided into three groups. The inflammatory factors studied included hypersensitive C-reactive protein (Hs-CRP), interleukin-6 (IL-6), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 33 publications
9
66
0
Order By: Relevance
“…CVT is an uncommon condition with an incidence of 1.3-1.6/100,000 in Western countries (10). Traditionally, the most prevalent aetiology of CVT was infections but nowadays aseptic CVT are more frequent.…”
Section: Case Reportmentioning
confidence: 99%
“…CVT is an uncommon condition with an incidence of 1.3-1.6/100,000 in Western countries (10). Traditionally, the most prevalent aetiology of CVT was infections but nowadays aseptic CVT are more frequent.…”
Section: Case Reportmentioning
confidence: 99%
“…Recently it is regarded that immune and coagulation systems are functionally connected [5,6]. Proin ammatory cytokines and other mediators have been described to be responsible for activating the coagulation system as well as down-regulating important physiologic anticoagulant pathways [7][8][9][10]. A previous study revealed that IL-6 could mediate thrombocytosis, platelet hyperreactivity, and accelerate extra-intestinal thrombosis associated with experimental colitis [11].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that a high level of HBs-Ab in all CVT patients, but there was no signi cant difference between the headache and non-headache groups. Previous studies reported that CVT patients had a higher HBs-Ag-positive rate compared to health controls 15,17 , indicating HBV infection may be a risk factor for CVT 17 .…”
Section: Discussionmentioning
confidence: 93%
“…Infection has been considered as one of the most common causes of CVT 15 and the neutrophil-tolymphocyte ratio is signi cantly associated with poor outcomes at discharge 15,16 . Our study showed that head and face infection or upper respiratory infection occurred in 27.68% (26/69) of the patients.…”
Section: Discussionmentioning
confidence: 99%